(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This study examines pedagogical technique as a fundamental professional competence of primary school teachers. Pedagogical technique is conceptualized as an integrated system encompassing verbal communication, nonverbal behavior, emotional regulation, and classroom management strategies. Using a qualitative conceptual research design, the study synthesizes national and international scholarly literature to analyze the role of pedagogical technique in improving instructional effectiveness. The findings indicate that systematically developed pedagogical technique significantly enhances student engagement, motivation, and the quality of classroom interaction in primary education settings.